KAJIAN YURIDIS PERKAWINAN SEORANG SUAMI DENGAN LEBIH DARI SATU ISTRI (Studi Kasus Putusan Nomor : 579/Pdt.G/2010/PA.Yk dan 321/Pdt.G/2011/PA.Yk) - Puspita, A.A. Ayu Putu Erna ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study is to understand and analyze the judge suitability considerations in giving permission a husband marriage with more than one wife, in the religious court decisions No. 579/Pdt.G/2010/PA.Yk and 321/Pdt.G/2011/PA.Yk with the Marriage Act and the Compilation of Islamic Law, and to understand the establishment of joint property in the case of a husband marriage with more than one wife in the religious court decisions No. 579/Pdt. G/2010/PA.Yk and 321/Pdt.G/2011/PA.Yk. This study is a normative legal research which is done by researching library materials or secondary data. The secondary data is including primary legal materials, secondary and tertiary. To support and supplement the data, then do the interview with sources. The collected data is analyzed with qualitative methods (case study). Based on studyconducted by the author, it is concluded, first, the basic consideration of the judges in giving a husband a marriage license with more than one wife, in this decision, it is not all in accordance with the Marriage Act and the Compilation of Islamic Law. Second, the establishment of joint property, in the case of a husband marriage with more than one wife, in this decision, namely to set joint property which is filed by the applicant and the respondent by the Religious Court Judge of Yogyakarta, then these treasures are joint property, the applicant and the respondent, stand-alone, and separate the joint property, which will be formed between the applicant and the second wife candidate, the applicant must not interfere with accountability, the applicant’s property and the respondent that has been there all along.